Multifaceted Roles of cAMP Signaling in the Repair Process of Spinal Cord Injury and Related Combination Treatments - Zhou, Gang; Wang, Zhiyan; Han, Shiyuan; Chen, Xiaokun; Li, Zhimin; Hu, Xianghui; Li, Yongning; Gao, Jun (Frontiers in Molecular Neuroscience, 2022)
Spinal cord injury (SCI) results in multiple pathophysiological processes, including blood–spinal cord barrier disruption, hemorrhage/ischemia, oxidative stress, neuroinflammation, scar formation, and demyelination. These responses eventually lead to severe tissue destruction and an inhibitory environment for neural regeneration. cAMP signaling is vital for neurite outgrowth and axonal guidance, stimulating intracellular cAMP activity significantly promotes neuronal survival and axonal regrowth after injury. However, neuronal cAMP levels in adult CNS are relatively low and will further decrease after injury. Targeting cAMP signaling has become a promising strategy for neural regeneration over the past two decades. Furthermore, studies have revealed that cAMP signaling is involved in the regulation of glial cell function in the microenvironment of SCI, including macrophage/microglia, reactive astrocytes, and oligodendrocytes. cAMP-elevating agents in the post-injury milieu increase the cAMP levels in both neurons and glial cells and facilitate injury repair through the interplay between neurons and glial cells and ultimately contribute to better morphological and functional outcomes. In recent years, combination treatments associated with cAMP signaling have been shown to exert synergistic effects on the recovery of SCI. Agents carried by nanoparticles exhibit increased water solubility and capacity to cross the blood–spinal cord barrier. Implanted bioscaffolds and injected hydrogels are potential carriers to release agents locally to avoid systemic side effects. Cell transplantation may provide permissive matrices to synergize with the cAMP-enhanced growth capacity of neurons. cAMP can also induce the oriented differentiation of transplanted neural stem/progenitor cells into neurons and increase the survival rate of cell grafts. Emerging progress focused on cAMP compartmentation provides researchers with new perspectives to understand the complexity of downstream signaling, which may facilitate the clinical translation of strategies targeting cAMP signaling for SCI repair